The size-and shape-controlled synthesis of silver nanoparticles by solvothermal method - Nguyen Thi Ngoc Linh; Le The Tam; Ngo Thanh Dung; Le Thi Thanh Tam; Ha Minh Nguyet; Nguyen Dinh Vinh; Bui Minh Quy; Nguyen Thi Hong Hoa; Nguyen Hoa Du; Le Trong Lu; et al. (Vietnam Journal of Science and Technology, 2023)
In this work, Ag nanoparticles (NPs) were fabricated by thermal decomposition of silver nitrate in organic solvents in the presence of sodium oleate (SOA) and 1-octadecanol (OCD-ol). The effects of different solvents and concentrations of OCD-ol on the morphology and properties of the Ag nanomaterials were investigated in detail. The structural analysis of the Ag nanomaterials showed good crystallinity. The TEM images of the samples showed that with the change in the fabrication conditions, different sizes and shapes of Ag nanomaterials were formed. The surface plasmon resonance (SPR) properties of the Ag NPs were influenced by their size and shape. The as-synthesized Ag NPs have potential applications in biomedical, catalysis, or electronics.